Desalination using renewable energy sources on the arid islands of South Aegean Sea. (1st January 2016) - Mentis, Dimitrios; Karalis, George; Zervos, Arthouros; Howells, Mark; Taliotis, Constantinos; Bazilian, Morgan; Rogner, Holger
Abstract: Water and energy supply are strongly interrelated and their efficient management is crucial for a sustainable future. Water and energy systems on several Greek islands face a number of pressing issues. Water supply is problematic as regards both to the water quality and quantity. There is significant lack of water on several islands and this is mainly dealt with tanker vessels which transport vast amounts of water from the mainland. At the same time island energy systems are congested and rely predominantly on fossil fuels, despite the abundant renewable energy potential. These issues may be addressed by combining desalination and renewable energy technologies. It is essential to analyse the feasibility of this possibility. This study focuses on developing a tool capable of designing and optimally sizing desalination and renewable energy units. Several parameters regarding an island's water demand and the desalination's energy requirements are taken into account as well as input data which concern technological performance, resource availability and economic data. The tool is applied on three islands in the South Aegean Sea, Patmos (large), Lipsoi (medium) and Thirasia (small). Results of the modelling exercise show that the water selling price ranges from 1.45 €/m 3 for the large island, while the corresponding value is about 2.6 €/m 3 for the small island, figures significantly lower than the current water cost (7–9 €/m 3 ). Highlights: Contribution to the dimensioning of desalination and RET units. Contribution to the calculation of economic indicators for investors. Planning and design tool for the Hellenic State. Assessment tool for other related investment plans. Desalinated water production cost significantly lower than the current one.